A morte digna, direito fundamental - Varalli, Janaina Thais Daniel (2017)
The main objective of the work is to investigate the right to a dignified death as a true fundamental right of the individual. The premise is that if national and international legislation protects the right to a dignified life, as can be seen from the systematic and teleological reading of articles 5 and 225 of the Federal Constitution and international documents such as the Universal Declaration of Human Rights, one must recognize the right to the dignified life in all the phases of existence of the subject, even when it is in terminal phase. In order to develop the study, the principles of bioethics and biolaw, the concepts of euthanasia, orthothanasia, assisted suicide and dysthanasia, as well as palliative care were analyzed. The role of the State as guarantor of the right to life was also analyzed, but also as a guarantor of freedom and autonomy in the private matters. Emblematic cases have been investigated in order to observe the current stage of discussion and legislation in Brazil and in the world. The right to a dignified death, whether through voluntary euthanasia or assisted suicide, is an unfolding of the right to a dignified life and can be exercised by those who are aware, informed of their clinical conditions and options, privileging the autonomous decision of the subject to submission to certain medical treatments and procedures and regarding the duration of life, which can be foreseen in the instrument called advance directives. If life is a right it can not become a real burden